2016
DOI: 10.1101/sqb.2016.81.030817
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Chemical Gradients in the Tumor Microenvironment Regulate Tumor Cell Invasion, Migration, and Metastasis

Abstract: Cancer metastasis requires the invasion of tumor cells into the stroma and the directed migration of tumor cells through the stroma toward the vasculature and lymphatics where they can disseminate and colonize secondary organs. Physical and biochemical gradients that form within the primary tumor tissue promote tumor cell invasion and drive persistent migration toward blood vessels and the lymphatics to facilitate tumor cell dissemination. These microenvironment cues include hypoxia and pH gradients, gradients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
121
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(123 citation statements)
references
References 168 publications
0
121
1
Order By: Relevance
“…Cells can utilize different migration mechanisms and hence display a high plasticity. Moreover, the cells alter their signal transduction pathways and remodel dynamically their intracellular cytoskeleton and focal adhesion, facilitating cell–matrix interaction dependent on the surrounding physical confinement . It has been found that these physical parameters, causing the adaptation of the cells to their physical constraints, need to be determined in order to decrease accessible motility and hence the malignant progression of cancer .…”
Section: Two Opposing Roles Of the Tumor Stromamentioning
confidence: 99%
“…Cells can utilize different migration mechanisms and hence display a high plasticity. Moreover, the cells alter their signal transduction pathways and remodel dynamically their intracellular cytoskeleton and focal adhesion, facilitating cell–matrix interaction dependent on the surrounding physical confinement . It has been found that these physical parameters, causing the adaptation of the cells to their physical constraints, need to be determined in order to decrease accessible motility and hence the malignant progression of cancer .…”
Section: Two Opposing Roles Of the Tumor Stromamentioning
confidence: 99%
“…As noted above, cells are exquisitely sensitive to mechanical signals from the extracellular environment, and in cancer cells, the responses to matrix stiffness can have downstream impacts on migration, proliferation, survival and invasiveness . Moreover, gradients in stiffness and the alignment of collagen fibers may influence directional cell migration by durotaxis and alignotaxis, respectively .…”
Section: The Tumor Microenvironment As a Target For Cancer Treatmentmentioning
confidence: 99%
“…Extending from aquated metal ions [M(H 2 O) n ] m+ , the study of defined coordination compounds with inert ligands such as NH 3 3+ ) with ECM components such as integrins and GAGs has rich and multiple applications in this new area of endeavor in the field of bioinorganic chemistry distinct from protein and DNA/RNA interactions [1]. The inherent ability to alter oxidation state, coordination number and geometry, as well as substitution lability of coordinated ligands allows the study of a wide variety of structure and function on the 'heparin/HS' interactome.…”
Section: Platinum Coordination Compounds In Cancer Cell Migration Andmentioning
confidence: 99%